Mobilization of Deposit in Commercial Banks of Ethiopia: Conceptual Model development through Literature Review - Kant, Shashi; Dugo Debesso (RADINKA JAYA UTAMA PUBLISHER, 2023)
The purpose of this study is to provide a conceptual framework and determine the factors influencing deposit mobilization in Ethiopia's commercial banks using the literature that is currently accessible. The bank's yearly incremental deposit plan, which calls for the easy mobilization of a sizable sum of money from the communities, is no longer the optimum method for undertaking deposit mobilization. The literature relating to factors influencing deposit mobilization at Ethiopia's commercial banks is presented in this overview of the literature. As a result, there are three sections to the literature review. The introduction linked to overviews of deposit mobilization in Ethiopian commercial banks and factors affecting deposit mobilization is covered in the first portion of the literature review. The second portion looks at empirical concerns regarding the factors influencing deposit mobilization. The conceptual framework for deposit mobilization is shown in the third section, followed by the literature gap of the evaluated literature. Researchers framed the conceptual framework for the research's future course using the most recent available literature.